PENGEMBANGAN E-LEARNING BERBASIS MOODLE PADA MATA PELAJARAN SIMULASI DIGITAL DI SEKOLAH MENENGAH KEJURUAN - Manggala, Esa; Asrori, Mohammad; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is intended to know the process of developing moodle based e-learning on simulasi digital., making moodle based e-learning developed in simulasi digital. and describe kelayakkan through learners' response to moodle-based e-learning developed in the program Study simulasi digital. This research is a research reasearch and Development (R & D) by using Borg and Gall development model. Product assessment is done by one material expert, one media expert, one design expert, and 42 students of Chemical Engineering SMK SMTI Pontianak. The development procedure contains 10 stages, ie stage, Research and information collecting, Planning, Develop preliminary form of product, Product Validation, Main product revision, Try Out testing, Main product revision, Field Try Out testing, Final product revision, Dessemination and impiemantatíon. This research uses qualitative approach. Based on the average one-try try out testing test, the average yield is 3.37 with the criteria "very feasible". On average small group test try out testing showed an average yield of 3.18 with "feasible" criteria. On average Field Try Out testing tests show an average yield of 3.36 with the criteria "very feasible". Key words: e-learning, moodle, learning, digital simulation.